Simon-Pierre Perret and Marie-Laure Ragot, Paul Dukas (2007) - Watson, Laura (Journal of the Society for Musicology in Ireland, 2008)
A review of Simon-Pierre Perret and Marie-Laure Ragot, Paul Dukas (Paris: Fayard, 2007), ISBN: 978-2-213-63329-9, 557 pp, €30